The Implementation Of Demonstration Method In Enhancing Arabic Language Learning Outcomes Among MI Aisyiyah Students - Rahmat, Nur; Wajdi, Muh Barid NIzarudin (STAI Miftahul Ula Nganjuk, 2023)
The implementation of the demonstration method aims to improve Arabic language learning outcomes. This study also seeks to identify the supporting and inhibiting factors associated with this method. A qualitative approach was employed, with the demonstration method specifically applied to the topic of